Ultrathin films for the transfer of antimicrobial agents to medical devices
Patent Information
- Application Number
- JP2023572591
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-24
- Filing Date
- 2022-05-24
- Publication Date
- 2025-04-22
AI Technical Summary
Existing orthopedic implants face challenges in imparting antimicrobial properties without interfering with their interlocking functionality and fit tolerances, leading to issues such as loosening or instability due to thick coatings or interference with tissue ingrowth.
The use of ultra-thin biodegradable polymer films impregnated with vaporizable antimicrobial agents, applied to orthopedic implants and components, creates a clinically effective zone of inhibition without compromising the interlocking function or fit tolerances, achieved by coating weights of 50-250 μg/cm² and surface area concentrations of 5-85 μg/cm² for the antimicrobial agent.
The solution effectively reduces microbial growth at surgical sites while maintaining the integrity and functionality of orthopedic implants, ensuring secure fixation and compatibility with tissue ingrowth, with a clinically significant zone of inhibition lasting up to 72 hours.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of U.S. Provisional Patent Application Publication No. 63 / 192,339, filed May 24, 2021, the entire contents of which are incorporated herein by reference.
[0002] FIELD OF THEINVENTION The present disclosure relates to orthopedic implants having antimicrobial properties. [Background technology]
[0003] Many individuals receive orthopedic implants each year as a result of orthopedic trauma or joint replacement procedures. In the United States, more than 600,000 knee prostheses and more than 300,000 hip prostheses are implanted each year according to the American Academy of Orthopedic Surgeons. Over one million patients receive metal implants each year to treat broken bones. Implant-associated infection is one of the most serious potential complications associated with orthopedic implants, with infection rates of over 10% in some high-risk procedures and patient groups. The cost of treating implant-associated infections is significant, as treatment often requires surgical removal of the infected implant and long-term treatment with antibiotics.
[0004] Implant-associated infections occur when bacteria contaminate a surgical wound site, attach to a surgical implant, and begin to grow. Bacteria growing on the implant surface often form a biofilm, where the bacteria secrete a protective extracellular matrix and the metabolic activity of the bacteria is significantly reduced. This biofilm phenotype protects the bacteria from the patient's immune system and systemic antibiotics, which makes the treatment of implant-associated infections very difficult and expensive.
[0005] One solution to prevent implant-associated infections is to treat the surface of surgical implants to prevent bacterial growth and attachment. Surgical implants have been developed that are coated with antibiotics or antimicrobial compounds to kill bacteria at the surgical wound site or on the implant surface before they can attach to and grow on the implant. Examples include antimicrobially coated pacemaker pouches (TYRX™ Absorbable Antimicrobial Envelope), orthopedic implants (ETN PROtect), surgical graft materials (XenMatrix™ AB Surgical Graft), and sutures (VICRYL® Plus Antimicrobial Suture).
[0006] Methods have been disclosed for vapor transferring a vaporizable antimicrobial agent to a medical device, such as a suture, by placing the device within an inner package having a source of antimicrobial agent, covering the inner package with an outer package, and exposing the device and package to conditions of time, temperature, and pressure sufficient to vapor transfer the antimicrobial agent from the source of antimicrobial agent to the device (e.g., U.S. Pat. Nos. 7,513,093; 8,112,973; 8,133,437; 8,156,718; 8,668,867; 8,960,422; 9,044,531; 9,149,273; 9,474,524; 9,597,067; and 9,597,072). This vapor transfer process has been demonstrated to be successful in transferring antimicrobial agents into polymeric or paper materials (eg, surgical sutures or packaging materials).
[0007] When applied to orthopedic implants, coatings with antibiotics such as gentamicin can interfere with the ability of components (such as bone plates connecting bone fasteners) to join and remain securely connected to one another after implantation and degradation of the coating. For example, a PLGA coating containing particulate gentamicin can interfere with the locking function of trauma plates secured with bone fasteners, causing a significant reduction in the amount of torque required to release the fasteners from the plate. Summary of the Invention [Problem to be solved by the invention]
[0008] There remains a need for systems and techniques that impart antimicrobial properties to orthopedic implants and their components without interfering with the articulating function of such devices. [Means for solving the problem]
[0009] Provided herein is an orthopedic implant or a component of an orthopedic implant for reducing microbial growth at a surgical site, the orthopedic implant comprising: a body defining an outer body surface; a biodegradable polymeric film disposed along at least a portion of the outer body surface; and a vaporizable antimicrobial agent disposed within the biodegradable polymeric film, wherein one or more of the following apply: the biodegradable polymeric film has a vaporizable antimicrobial agent concentration of about 50-250 μg / cm 2 The vaporizable antimicrobial agent has a surface area coating weight of about 5 to 85 μg / cm 2 or the surface area concentration of the antimicrobial agent is sufficient to produce an effective zone of inhibition of at least 0.5 mm from the periphery of the outer surface.
[0010] Also provided herein are methods for preparing an orthopedic implant or a component of an orthopedic implant that reduces microbial growth at a surgical site.
[0011] The present disclosure also provides a system for reducing microbial infection at an orthopedic implant surgical site, a kit including at least one orthopedic implant body and a plurality of bone fasteners that each reduce microbial infection at an orthopedic implant surgical site, and a method for reducing loss of release torque resulting from antimicrobial treatment of an orthopedic implant system. [Brief description of the drawings]
[0012] [Figure 1A] Polymer pellets are used to tumble stainless steel orthopedic implant components to provide results of an evaluation of their ability to coat the surfaces of such components. [Figure 1B] Polymer pellets are used to tumble stainless steel orthopedic implant components to provide results of an evaluation of their ability to coat the surfaces of such components. [Figure 1C] Polymer pellets are used to tumble stainless steel orthopedic implant components to provide results of an evaluation of their ability to coat the surfaces of such components. [Figure 2A] We provide the results of an evaluation of the ability of tumbling and dip coating to produce polymeric coatings capable of retaining antimicrobial agents to provide a clinically effective zone of inhibition on the coated component. [Figure 2B] We provide the results of an evaluation of the ability of tumbling and dip coating to produce polymeric coatings capable of retaining antimicrobial agents to provide a clinically effective zone of inhibition on the coated component. [Figure 2C] We provide the results of an evaluation of the ability of tumbling and dip coating to produce polymeric coatings capable of retaining antimicrobial agents to provide a clinically effective zone of inhibition on the coated component. [Figure 3A]1 illustrates the results of an evaluation of the post-use opening torque of a conventional polymer coating with particulate gentamicin and a biodegradable polymer film of the present invention containing triclosan, respectively. [Figure 3B] 1 illustrates the results of an evaluation of the post-use opening torque of a conventional polymer coating with particulate gentamicin and a biodegradable polymer film of the present invention containing triclosan, respectively. [Figure 4] 1 provides a flow chart for performing adherence and growth bacterial colony formation studies. [Diagram 5] Illustrates the migration of triclosan to an ultra-thin poly(L-lactide) film coated stainless steel locked compression plate at 130° C. in an all-metal container. [Figure 6] Shown are S. aureus zones obtained from 130°C triclosan vapor transfer-treated wound plates with either a bare electropolished stainless steel surface or an annealed ultrathin poly(L-lactide) membrane, and samples were either immediately placed on agar-injected plates or incubated in phosphate-buffered saline for 1, 24, or 72 h. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The inventive subject matter disclosed herein may be more readily understood by reference to the following detailed description taken in conjunction with the accompanying examples, which form a part of this disclosure: It is to be understood that the invention is not limited to the specific components, methods, or parameters described and / or illustrated herein, and that the terminology used herein is for the purpose of describing particular embodiments by way of example only, and is not intended to limit the invention as claimed.
[0014] The entire disclosure of each patent, patent application, and publication cited or described in this specification is hereby incorporated by reference.
[0015] As used above, and throughout this disclosure, the following terms and abbreviations shall be understood to have the following meanings, unless otherwise indicated:
[0016] In this disclosure, unless expressly stated otherwise, the singular forms "a," "an," and "the" include plural references and a reference to a particular numerical value includes at least that particular value. Thus, for example, a reference to a "polymer" is a reference to one or more such polymers and equivalents thereof known to those of skill in the art, and so forth. Furthermore, when indicating that a particular element "can be" X, Y, or Z, such use is not intended to exclude other options for that element in all instances.
[0017] When values are expressed as approximations by use of the antecedent "about," it is understood that the particular value forms another embodiment. In general, use of the term "about" indicates approximations that may vary depending on the desired properties sought to be obtained by the disclosed subject matter and should be interpreted in the specific context in which it is used based on its function. In some embodiments, "about X" (where X is a numerical value) refers to ±10% of the recited value, inclusive. For example, the phrase "about 8" can refer to values from 7.2 to 8.8, inclusive. This value can include "exactly 8." When present, all ranges are inclusive and combinable. For example, when reciting a range of "1 to 5," the recited range should be construed to optionally include ranges such as "1 to 4," "1 to 3," "1 to 2," "1 to 2 and 4 to 5," "1 to 3 and 5," etc. Additionally, when a list of alternatives is expressly provided, such list can also include embodiments in which any of the alternatives may be excluded. For example, if a range of "1 to 5" is described, such description may support a situation in which any of 1, 2, 3, 4, or 5 is excluded. Thus, a statement of "1 to 5" may support "1 and 3 to 5, but not 2" or simply "2 is not included."
[0018] As used herein, "zone of inhibition" (ZOI) refers to the distance measured from the periphery of an implant within which there are no measurable microbial colony forming units (e.g., microbial activity) when the implant is placed in an in vitro environment inoculated with a known amount of colonizing microorganisms. In certain references, the ZOI is measured as the total cross-sectional length (e.g., diameter) of the area within which there is no measurable microbial activity, which may include the dimensions of the implant as well.
[0019] As used herein, "clinically effective zone of inhibition" means a ZOI measurement of at least 0.5 mm around the implant that is free of measurable bacterial growth.
[0020] "Vaporizable," when used with respect to a chemical compound, such as an antimicrobial agent, means a compound that can evaporate when exposed to temperatures above 50° C. under ambient pressure conditions.
[0021] As explained above, orthopedic implants are susceptible to microbial contamination, and previous efforts to impart antimicrobial properties have led to interference with the ability of components (such as bone plates connecting bone fasteners) to interlock and remain securely connected to one another after implantation. In many cases, there are specific tolerances for an orthopedic implant to achieve a proper fit (e.g., an IM nail entering the femoral marrow), and in such cases, it is unacceptable for the implant to include a coating that prevents the implant from meeting such tolerances. Oversized implant diameters would result in the implant becoming loose or unstable due to thick coatings that subsequently degrade. In addition, implants that are configured to have spaces for tissue ingrowth would be incompatible with thicker coatings that occlude some or all of those spaces, thereby preventing natural tissue remodeling via ingrowth into the implant. For this reason, it is essential that any strategy for imparting antimicrobial properties be compatible with all intended uses of the orthopedic implant.
[0022] The inventors have surprisingly discovered that by using an extremely thin biodegradable coating impregnated with an antimicrobial agent, orthopedic implants and their components can be endowed with antimicrobial properties within a clinically significant zone of inhibition, while avoiding interference with the interlocking functions essential to the ability of the implant to remain securely in place at the surgical site, and optionally avoiding situations where the implant becomes incompatible with fit tolerances and tissue ingrowth.
[0023] Accordingly, there is provided herein an orthopedic implant or a component of an orthopedic implant for reducing microbial growth at a surgical site, comprising a body defining an outer body surface, a biodegradable polymeric film disposed along at least a portion of the outer body surface, and a vaporizable antimicrobial agent disposed within the biodegradable polymeric film, wherein one or more of the following apply: the biodegradable polymeric film has a vaporizable antimicrobial agent concentration of about 50-250 μg / cm 2 The vaporizable antimicrobial agent has a surface area coating weight of about 5 to 85 μg / cm 2 or the surface area concentration of the antimicrobial agent is sufficient to produce an effective zone of inhibition of at least 0.5 mm from the periphery of the outer surface.
[0024] Any orthopedic implant or orthopedic implant component can be used according to the present disclosure. An orthopedic implant is understood to be an implantable medical device that is a prosthesis used to help repair damaged bone or replace bone. An exemplary and non-limiting list of suitable orthopedic implants according to the present disclosure includes bone plates, intramedullary nails, bone screws, pins, spinal rods, K-wires, intervertebral disc replacements, metal compression staples (e.g., Nitinol), metal meshes such as those used in craniomaxillofacial applications, external fixation screws or pins (e.g., Schanz screws and Steinmann pins), and joint replacement components used in hip, knee, and shoulder replacement procedures, such as acetabular cups, femoral stems, tibial trays, artificial patellas, and femoral condylar components.
[0025] As described, the orthopedic implant defines an outer surface. The outer surface according to an embodiment may comprise a metal or metal alloy, a polyaryletherketone (PAEK) or copolymers thereof, or a polyalkene or copolymers thereof, or any combination of the above materials. Suitable metals may include, for example, titanium, stainless steel, nickel, cobalt, chromium, and metal alloys thereof. A preferred polyalkene is polyethylene or copolymers thereof. Suitable examples include high density polyethylene (HDPE), ultrahigh molecular weight polyethylene (UHMWPE), medium density polyethylene (MDPE), ultralow molecular weight polyethylene (ULMWPE), high molecular weight polyethylene (HMWPE), high density cross-linked polyethylene (HDXLPE), cross-linked polyethylene (PEX or XLPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), or very low density polyethylene (VLDPE), as well as blends or copolymers thereof. Under certain high temperature conditions, as further described below, one skilled in the art can determine which polyalkenes or copolymers thereof have the necessary chemical properties to withstand conditions requiring high temperatures, for example, above 100°C, without thermal degradation or other undesirable effects.Suitable examples of PAEK polymers include, but are not limited to, polyetheretherketone (PEEK) carbon reinforced PEEK, polyetherketoneketone (PEKK), polyetherketone (PEK), or polyetherketoneetherketoneketone (PEKEKK), or blends or copolymers thereof.
[0026] The biodegradable polymeric film is effectively integrally formed with and attached to the underlying orthopedic implant or component thereof. The surface area coating weight of the biodegradable polymeric film is about 60-230 μg / cm 2 In some embodiments, the surface area coating weight of the biodegradable polymer thin film can be about 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, or 250 μg / cm 2 It is.
[0027] The biodegradable polymer thin film may comprise a poly(α-hydroxy ester) polymer. For example, the biodegradable polymer thin film may comprise poly(glycolic acid) (PGA), poly(lactic acid) (PLA), poly(lactic-co-glycolic acid) (PLGA), poly(ε-caprolactone) (PCL), or any copolymer or mixture thereof. In some embodiments, the biodegradable polymer thin film comprises poly(l-lactic acid) (PLLA), poly(d-lactic acid) (PDLA), poly(d, l-lactic acid) (PDLLA), or any copolymer or mixture thereof.
[0028] In one embodiment, the vaporizable antimicrobial agent is about 5-85 μg / cm 2 For example, the antimicrobial agent has a surface area concentration of about 45-55 μg / cm 2 In some embodiments, the vaporizable antimicrobial agent can have a surface area concentration of about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, or 85 μg / cm 2 has a surface area concentration of
[0029] The vaporizable antimicrobial agent can be any compound or substance that provides the ability to reduce the formation of microbial colony forming units on the surface of an orthopedic implant, preferably within the zone of inhibition around the implant. In certain embodiments, the vaporizable antimicrobial agent is a halogenated hydroxyl ether, an acyloxydiphenyl ether, or a combination thereof. In particular, the antimicrobial agent can be a halogenated 2-hydroxydiphenyl ether and / or a halogenated 2-acyloxydiphenyl ether, for example, as represented by the following formula:
[0030] [ka]
[0031] In the above formula, each Hal represents the same or different halogen atom, Z represents hydrogen or an acyl group, w represents a positive natural number ranging from 1 to 5, and each of the benzene rings is preferably ring A, but may also contain one or more lower alkyl groups, lower alkoxy groups, allyl groups, cyano groups, amino groups, or lower alkanoyl groups that may be halogenated.Preferably, the lower alkyl groups and lower alkoxy groups useful as substituents on the benzene ring include methyl groups or methoxy groups, respectively.Halogenated lower alkyl groups and trifluoromethyl groups are preferred.
[0032] Antibacterial activity similar to that of the halogen-o-hydroxy-diphenyl ethers of the above formula can also be obtained using their O-acyl derivatives which undergo partial or complete hydrolysis under the conditions of practical use. The ethers of acetic acid, chloroacetic acid, methyl or dimethyl carbamic acid, benzoic acid, chlorobenzoic acid, methylsulfonic acid, and chloromethylsulfonic acid are particularly suitable.
[0033] One particularly preferred antimicrobial agent within the above formula is 2,4,4'-trichloro-2'-hydroxydiphenyl ether, commonly referred to as triclosan. Triclosan is a broad-spectrum antimicrobial agent used in a variety of products and is effective against a number of organisms commonly associated with SSIs. Such organisms include, but are not limited to, Staphylococcus spp., Staphylococcus epidermidis spp., Staphylococcus aureus spp., methicillin-resistant Staphylococcus epidermidis, methicillin-resistant Staphylococcus aureus, and combinations thereof.
[0034] In certain embodiments, the surface area concentration of the antimicrobial agent is sufficient to generate an effective zone of inhibition of about 0.5-4 mm from the periphery of the outer surface of the orthopedic implant or component thereof. For example, the surface area concentration of the antimicrobial agent may be sufficient to generate an effective zone of inhibition of about 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, 2.0, 2.25, 2.5, 2.75, 3.0, 3.5, 3.75, or 4 mm from the periphery of the outer surface of the orthopedic implant or component thereof. In some embodiments, the surface area concentration of the antimicrobial agent is sufficient to generate an effective zone of inhibition of about 1-2 mm from the periphery of the outer surface of the implant or component. The surface area concentration of the antimicrobial agent may be sufficient to generate an effective zone of inhibition according to the foregoing embodiments for up to about 6, 12, 18, 24, 36, 48, or 72 hours after implantation of the orthopedic implant or component into a human subject.
[0035] The biodegradable polymeric film may be present on some or all of the outer surface of the body of the implant or a component thereof. In an embodiment, the orthopedic implant includes an opening configured to receive a fastener, and the surface of the opening includes the biodegradable polymeric film. When the component of the orthopedic implant is a fastener, such as a threaded fastener including a head that contacts the surface of the opening of the orthopedic implant when implanted at a surgical site, the biodegradable polymeric film may be, for example, on the surface of the threaded portion of the fastener, the surface of the head, or both. In this manner, when the implant includes a bone plate or bone fastener, both the surface of the bone plate and the surface of the bone fastener that contact each other when the respective components are implanted at a surgical site include the biodegradable polymeric film. As disclosed more fully herein, the use of a biodegradable polymeric film according to the present disclosure on such surfaces of the orthopedic implant does not interfere with the physical interaction of the components that are configured to interlock with each other.
[0036] Also disclosed herein is a method for preparing an orthopedic implant or an orthopedic implant component that reduces microbial growth at a surgical site, comprising applying a biodegradable polymeric film onto a surface of the implant or implant component and incorporating a vaporizable antimicrobial agent into the film, wherein the vaporizable antimicrobial agent is present in an amount of about 5-85 μg / cm. 2 and the biodegradable polymer thin film has a surface area concentration of about 50-250 μg / cm 2 or a surface area concentration of antimicrobial agent is sufficient to produce an effective zone of inhibition of at least 0.5 mm from the periphery of the outer surface.
[0037] The application of a thin biodegradable polymer film onto the surface of the implant or implant component is in the range of about 50 to 250 μg / cm 2The coating may be performed by any technique capable of producing a surface area coating weight according to the present disclosure, such as a surface area coating weight of 1000 nm to 1500 nm. For example, the thin film is applied to the surface of the implant or implant component by dip coating, i.e., by immersing the implant or implant component in a coating solution comprising the biodegradable polymer. Other techniques may include spraying a coating solution comprising the biodegradable polymer onto the surface of the implant or component. Those skilled in the art can readily identify other acceptable approaches for applying a biodegradable polymer thin film onto the surface of an implant or implant component.
[0038] Antimicrobial agents may be incorporated into the thin film by vapor transfer from a source of the antimicrobial agent. Vapor transfer processes and suitable sources of antimicrobial agents are known to those of skill in the art, and any effective manner of achieving vapor transfer may be used.
[0039] According to the method, the properties of the orthopedic implant or components thereof, the biodegradable polymeric thin film, the vaporizable antimicrobial agent, the inhibition zone, and related features may follow the descriptions provided above in connection with the orthopedic implant or components of the orthopedic implant of the present disclosure for reducing microbial growth at a surgical site.
[0040] Also disclosed herein is a system for reducing microbial infection at an orthopedic implant surgical site comprising an orthopedic implant body defining an outer implant surface, the orthopedic implant body further defining one or more openings extending from an outer surface therethrough and configured to receive a bone fastener, the bone fastener configured to be disposed in the one or more openings to secure the orthopedic implant body to bone, the bone fastener defining the outer fastener surface, a biodegradable polymeric film disposed along at least a portion of the outer implant surface or the outer fastener surface, and a vaporizable antimicrobial agent disposed within the biodegradable polymeric film, the biodegradable polymeric film having a vaporizable antimicrobial agent concentration of about 50-250 μg / cm in a subject.2 and a surface area coating weight of about 5-85 μg / cm 2 wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibition zone of at least 0.5 mm from the periphery of the outer implant surface, or after use of an insertion torque suitable for implantation of the orthopedic implant body in a subject, the torque required to release the fastener from a corresponding opening in the orthopedic implant body is greater than or equal to about 90% of the torque required to release an uncoated, but otherwise identical fastener from a corresponding opening in an uncoated, but otherwise identical orthopedic implant body for up to five days after implantation of the orthopedic implant body.
[0041] According to the present system, the use of biodegradable polymeric thin films having the properties disclosed herein on the surfaces of orthopedic implants and fasteners does not prevent physical interaction of such components when configured to interlock with one another to secure the implant within a surgical site, e.g., on a bone surface of a subject. An important measure of whether a coating on the implant surface prevents such physical interaction is the ability of the implant system to retain the amount of torque required to release the respective components from one another, e.g., fasteners from corresponding openings in an orthopedic implant body, after use of an insertion torque suitable for implantation of the orthopedic implant body in a subject. In some embodiments of the present system, the torque required to release a fastener from a corresponding opening in an orthopedic implant body after use of an insertion torque suitable for implantation of the orthopedic implant body in a subject is about 90% or more of the torque required to release an uncoated and otherwise identical fastener from a corresponding opening in an uncoated but otherwise identical orthopedic implant body for up to five days after implantation of the orthopedic implant body in a subject. For example, after use of an insertion torque suitable for implantation of the orthopedic implant body within a subject, the torque required to release a fastener from a corresponding opening in the orthopedic implant body is greater than or equal to about 91, 92, 93, 94, 95, 96, 97, 98, or 99% of the torque required to release an uncoated and otherwise identical fastener from a corresponding opening in an uncoated but otherwise identical orthopedic implant body. Such release torque may be required for a period of up to 5 days, such as up to 6 hours, 12 hours, 18 hours, 24 hours, 36 hours, 48 hours, 60 hours, 72 hours, 84 hours, 96 hours, 108 hours, or 120 hours, after implantation of the orthopedic implant body in a subject.
[0042] According to the present system, the properties of the orthopedic implant or fastener, the biodegradable polymeric thin film, the vaporizable antimicrobial agent, the zone of inhibition, and other related features may follow the descriptions provided above in connection with the presently disclosed orthopedic implant or component of an orthopedic implant for reducing bacterial growth at a surgical site, and in connection with the presently disclosed methods for preparing an orthopedic implant or component of an orthopedic implant for reducing bacterial growth at a surgical site.
[0043] Also disclosed herein is a kit comprising at least one orthopaedic implant body defining an outer implant surface, the orthopaedic implant body further defining one or more openings extending from an outer surface therethrough and configured to receive a bone fastener, a plurality of bone fasteners configured to be disposed within the at least one opening of the orthopaedic implant body to secure the orthopaedic implant body to bone, each of the bone fasteners each defining an outer fastener surface, a biodegradable polymeric film disposed along at least a portion of the outer implant surface of each of the orthopaedic implant bodies, a biodegradable polymeric film disposed along at least a portion of the outer fastener surface of each of the bone fasteners, or both, and a vaporizable antimicrobial agent disposed within the biodegradable polymeric film, the biodegradable polymeric film having a vaporizable antimicrobial agent content of about 50-250 μg / cm 2 and a surface area coating weight of about 5 to 85 μg / cm2 of the vaporizable antimicrobial agent. 2wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibition zone of at least 0.5 mm from the periphery of the outer implant surface, or after use of an insertion torque suitable for implantation of the orthopedic implant body, the torque required to release one of the fasteners from a corresponding opening in one of the orthopedic implant bodies is greater than or equal to about 90% of the torque required to release an uncoated, but otherwise identical fastener from a corresponding opening in an uncoated, but otherwise identical orthopedic implant body, for up to five days after implantation of the orthopedic implant body in the subject.
[0044] The subject kits thus contain one or more orthopaedic implant bodies configured with including openings for receiving bone fasteners, as well as a plurality of bone fasteners for use in securing the orthopaedic implant bodies to bone, and to the extent necessary, the kits may include a plurality of orthopaedic implant bodies, each of the same or different types, as well as corresponding bone fasteners that differ individually as necessary for compatibility with a provided orthopaedic implant body. The kits may be arranged to include, for example, all of the implant components needed to complete a particular implant procedure.
[0045] According to the present kits, the properties of the orthopedic implant body or fastener, biodegradable polymeric thin film, vaporizable antimicrobial agent, inhibition zone, opening torque characteristics, and other related features may follow the descriptions provided above in connection with the presently disclosed orthopedic implant or component of an orthopedic implant for reducing microbial growth at a surgical site, in connection with the presently disclosed method for preparing an orthopedic implant or component of an orthopedic implant for reducing microbial growth at a surgical site, and in connection with the presently disclosed system for reducing microbial growth at an orthopedic implant surgical site.
[0046] The present disclosure also provides a method for reducing loss of opening torque resulting from antimicrobial treatment of an orthopedic implant system including an orthopedic implant body defining an outer implant surface, the orthopedic implant body further defining one or more openings extending from the outer implant surface through the implant body and configured to receive bone fasteners, the bone fasteners being configured to be disposed in the one or more openings to secure the orthopedic implant body to bone, the bone fasteners defining an outer fastener surface, the method including applying a biodegradable polymeric film to one or both of the openings, the corresponding outer fastener surface, and incorporating a vaporizable antimicrobial agent into the film, the biodegradable polymeric film having a vaporizable antimicrobial agent concentration of about 50-250 μg / cm. 2 and a surface area coating weight of about 5-85 μg / cm 2 wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibition zone of at least 0.5 mm from the periphery of the outer implant surface, or wherein after use of an insertion torque suitable for implantation of the orthopedic implant body in the subject, the torque required to release one of the fasteners from a corresponding opening in one of the orthopedic implant bodies is greater than or equal to about 90% of the torque required to release an uncoated, but otherwise identical fastener from a corresponding opening in an uncoated, but otherwise identical orthopedic implant body, for up to five days after implantation of the orthopedic implant body in the subject.
[0047] According to the present method, the properties of the orthopedic implant body or fastener, biodegradable polymeric thin film, vaporizable antimicrobial agent, inhibition zone, release torque characteristics, and other related features may follow the descriptions provided above in connection with the presently disclosed orthopedic implant or orthopedic implant component for reducing microbial growth at a surgical site, in connection with the presently disclosed method for preparing an orthopedic implant or orthopedic implant component for reducing microbial growth at a surgical site, in connection with the presently disclosed system for reducing microbial infection at an orthopedic implant surgical site, and in connection with the presently disclosed kit. EXAMPLES
[0048] The present invention is further defined in the following examples. It should be understood that these examples, while showing preferred embodiments of the present invention, are given only as illustrations and should not be interpreted as limiting the scope of the appended claims. From the above discussion and these examples, those skilled in the art can ascertain the essential features of the present invention, and can make various changes and modifications to the present invention to adapt it to various applications and conditions without departing from the spirit and scope thereof.
[0049] Example 1 - Conventional vapor transfer of antimicrobial agents to implant surfaces Vapor transfer of triclosan onto metal orthopedic implants was attempted according to the process described in U.S. Pat. No. 8,668,867 to determine whether the process described could effectively deposit triclosan onto metal surfaces.
[0050] 1) titanium alloy (Ti-6Al-7Nb (TAN)), 2) 316L stainless steel, and 3) approximately 0.55 mg / cm 2 A series of metal pins (approximately 4 mm x 30 mm) were tested, including TAN pins with a poly(D,L-lactide) (PLA) coating of 1000 nm.
[0051] Triclosan (IRGACARE MP Triclosan Lot No. 0013227542) was compounded at 2.56% by weight into the high density polyethylene (HDPE) sheets.
[0052] The pins were co-packaged with 0.62-0.66 grams of triclosan impregnated HDPE sheet (approximately 16 mg triclosan) into a four-layer packaging material suitable for EO sterilization, with an outer PET layer, a polyethylene layer, a foil moisture barrier, and an inner polyethylene heat seal layer with a foil layer (moisture barrier) disposed between the two. The package was EO sterilized and heat treated at 55°C for 4 hours.
[0053] After the EO sterilization and heat treatment process was completed, the antibacterial activity of the pins was measured. 9 CFU / mL of S. aureus were spread onto the preformed plates with a sterile cotton swab and the pin was gently pressed onto the surface of the spread plate but did not penetrate the agar medium. The plates were incubated for 24 hours and then the ZOI was measured for each pin.
[0054] The total zone was measured across the width (short axis) of the implant and the results were as follows: Stainless: minimal observation zone of reduced proliferation (no ZOI), TAN: minimal observation zone of reduced proliferation (no ZOI), TAN-PLA: 12.4mm ZOI.
[0055] Accounting for the implant width (approximately 4.0 mm) and dividing by 2 to account for the ZOI on each side of the implant, the circumferential ZOI for each implant type was as follows: Stainless: not observed, TAN: not observed, TAN-PLA: 4.2 mm.
[0056] Thus, the results showed that only the polymer-coated pins (TAN-PLA) were able to provide a clinically effective ZOI, whereas pins with only a metal substrate surface were unable to retain clinically significant amounts of triclosan.
[0057] Example 2 - Polymer transfer to implant surface by tumbling Tumbling of stainless steel materials with polycaprolactone pellets at temperatures between 45 and 60°C was evaluated. Six 4 mm diameter and 30 mm long 316L stainless steel pins and one 4-hole trauma plate (DePuy Synthes 224.541 80 mm long x 13.5 mm wide x approximately 5 mm thick) were placed in a rubber octagonal tumbling chamber along with 245 grams of polycaprolactone pellets (Polysciences 26290-600, MW 80,000). Temperature was increased at 45, 50, 32, 54, and 56°C with tumbling periods of 1.5 to 2 hours at each temperature. Tumbling medium (322 grams) was added and heating was continued (56, 58, and 60°C). Observations of polycaprolactone appearance, metal part appearance, and metal part mass were observed at each temperature increment.
[0058] The pin mass did not change appreciably over the range of heating (Figure 1A). The change in mass is in tenths of a milligram with the same resolution as the balance. However, a downward trend in the mass of the trauma plate was observed (Figure 1A). No migration of polycaprolactone could be measured by mass balance. However, the air-water contact angles of the pin and tumbling medium changed significantly, indicating modification of the surface with polycaprolactone. Microscopy demonstrated evidence of migration of PCL to the surfaces of the pin (Figure 1B) and trauma plate (Figure 1C), but no attachment of PCL to the locking threads was observed (Figure 1C). This has the advantage of avoiding polymer contamination of the locking mechanism of the trauma plate.
[0059] Example 3 - Comparison between PCL tumbling, ultra-thin dip coating, and traditional polymer coating of orthopedic implants Samples were prepared for the purpose of evaluating the minimum polymer coating that could sustain antimicrobial activity. The samples were 54 mm x 12.5 mm 316L plates, a rectangular representation of the wound plate suitable for zone of inhibition studies, called "flat plates". Two specific processes were used: manual dip coating in a 4.5% wt / wt polylactide-ethyl acetate solution and tumbling at 56°C for 16 hours in polycaprolactone pellets (245 grams Polysciences 26290-500, MW 80,000) and tumbling medium (322 grams). Manual dip coating yielded 53 μg / cm 2 Polycaprolactone tumbling did not produce an increase in sample mass; rather, the tumbling process removed mass from the 316L sample (28 mg from a 15.7 gram 316L plate). However, coating of the sample with polycaprolactone was confirmed by microscopic observation and an increase in the air-water contact angle (Figure 2A).
[0060] Triclosan vapor migration from PE-triclosan sheet test samples was performed by placing 0.65±0.02 grams of triclosan-containing PE sheet into a foil sterilization pouch along with the material to be treated. The pouch was heat sealed and triclosan migration was completed at 55° C. for approximately 4 hours.
[0061] The following samples were treated with triclosan in the same batch: 316L Stainless Steel Pin Diameter 4mm x Length 30mm, 316L flat plate, 53μg / cm 2 Polylactide coated 316L plates, 316L pins PCL tumbled at 60°C from Example #2, 316L flat plate with PCL tumbled at 56℃, 19mm PEEK disc, Rapidsorb 85:15 PLGA plate (Synthes PN 851.421.01S), Porous polyethylene (Synthes PN 08.510.130S cut to 13mm x 50mm).
[0062] Three 0.59 mg / cm from Example 1 2 Polylactide coated pins were also included. For these samples, triclosan migration was observed during both EO sterilization and 4 hour, 55°C oven treatment.
[0063] The antimicrobial activity of the triclosan transfer-treated samples was evaluated by zone of inhibition assay performed after a phosphate-buffered incubation period (Figure 2C). 8 CFU / mL of cultures of S. aureus ATCC 25923 were spread on the preformed plates with a sterile cotton swab and gently pressed onto the surface of the plate where the sample was spread. Samples were either removed from the pouch and placed directly on the ZOI or samples were placed in 12 mL of PBS for 15 minutes or 24 hours. Samples incubated in PBS were further rinsed with 12 mL of PBS before being placed on the ZOI dish. Care was taken to place the samples on the plate where the ZOI was spread with the other side of the PE strip facing the bacteria. This presents a worst case scenario for triclosan migration from the PE strip in the pouch. After 24 hours of bacterial growth, the zone width and sample width were measured. The inhibition zone was measured as the margin from the edge of the implant calculated as (zone width-sample width) / 2.
[0064] Table 1 describes the measured zones of inhibition around metal pins and plates and exemplary polymeric medical device materials. "Shadow" refers to minimal observed area of reduced proliferation (no ZOI). "Localized" means that the zones were only observed in some areas adjacent to the sample, i.e., no consistent zone of inhibition was observed, but some activity was present.
[0065] [Table 1]
[0066] The solid polymer samples consistently produced a zone of inhibition with immediate placement on the plate spread with S. aureus or when placement was after 15 minutes of incubation in PBS. After 24 hours of incubation in PBS with the solid polymer samples, there was a zone or localized activity. No zones were observed adjacent to the stainless steel pin or plate, however, an ultra-thin coating could improve zone durability to incubation and rinsing in PBS. The PCL tumbling process produced an immediate zone of inhibition, but not one that survived a PBS rinse. An ultra-thin 0.53 μg / cm 2 A polylactide coating of 0.59 mg / cm on a titanium alloy pin produced a zone that survived incubation for 15 min, but only localized activity after 24 h of incubation. 2 Thicker coatings of polylactide produced robust zones that withstood 24-hour pre-elution. The minimum coating weight to produce a zone of inhibition after 24-hour pre-incubation in PBS ranged from 53 to 590 μg / cm for triclosan transfer conducted at 55°C for 4 hours from triclosan formulated at 2.56% on polyethylene strips. 2 It is.
[0067] Example 4 - Fabrication and evaluation of inhibition zones Polylactide dip coating solutions of 5% polylactide in ethyl acetate (Evonik Resomer 203S) and 8% polylactide in ethyl acetate were prepared and used to dip coat a 7-well 3.5 LCP 316L trauma plate (DPS PN223.571 98 mm long x 11 mm wide). The plate was coated with the solutions by clamping the specimen horizontally in a stainless steel mesh tray and manually dipping it into each solution and then withdrawing it. The specimens were weighed before coating and after drying overnight to determine the thickness of the 22.72 cm2 specimen. 2 The coating mass per area was calculated: 102±5 μg / cm for a 5% polylactide solution in ethyl acetate. 2The 8% solution produced a coating weight of 229±14 μg / cm 2 Coating in a low viscosity polymer solution has the advantage of coating many different part sizes or shapes with a single method.
[0068] The wound plates were co-packaged in a foil pouch with 0.67±0.02 grams of polyethylene sheeting formulated with 2.56% triclosan. Triclosan vapor transfer was performed for 4 hours and 31 minutes in a preheated 55° C. oven. Cooled samples were evaluated for zone of inhibition either directly from the package or after pre-elution in PBS for 15 or 24 hours. Zone of inhibition analysis was performed by the pour plate method as follows: 10 in 20 mL of TSB prepared in the laboratory 9 A bacterial inoculum of Staphylococcus aureus at a concentration of CFU / mL is prepared by overnight incubation in a 37° C. shaker. · Obtain an OD600 reading of the diluted stock of the overnight culture to determine the stock concentration by spectrophotometry. Dilute the bacterial concentration from the stock concentration to 10 with 0.3% TSB, making sure to forcefully aspirate up and down with a serological pipette to break up any clumps of colonies. 5 Adjust to CFU / mL. Determine the initial cell stock concentration by plating the following dilutions in triplicate on TSA-L plates: 10 2 CFU / mL. · Prepare the TSA (autoclave 20 g of tryptic soy agar in 500 mL of ultrapure water at 121 °C for 30 min) and cool the agar in a water bath at 45 °C. Once the temperature of the agar reaches 45 °C, take a sterile Petri dish. Add the inoculum (1.00E+05 CFU / mL) to the center of the Petri dish, then slowly pour in 15 mL of TSA. Close the lid and swirl the Petri dish to mix the inoculum with the agar. Avoid creating air bubbles. Place the test sample in the center of the Petri dish using sterile forceps. Place the plate on a wavy, undisturbed surface for approximately 10 minutes to allow the agar to gel completely. Incubate the plate at 37°C for 24 hours. -Measure the zone of inhibition by image analysis.
[0069] As shown in Table 2 below, the resulting zones were 102 and 229 μg / cm 2 This shows that a polylactide (Resomer 203S) coating allows triclosan migration at 55° C. and 4.5 hours, producing a zone of inhibition that persists for at least 24 hours.
[0070] [Table 2]
[0071] Example 5 - Evaluation of the opening torque of polylactide coated trauma plates against 40% gentamicin sulfate in poly(lactide-co-glycolide) coated plates The anchored wound plating construct must remain anchored after implantation. Approximately 3.5 mg / cm 2 Poly(lactide-co-glycolide) with 40% particulate gentamicin sulfate coated on the wound plate at a coating weight of 102 μg / cm with vapor transfer triclosan prepared in Example #04. 2 and 229 μg / cm 2Polylactide was compared against two ultra-thin polylactide coatings. A calibrated torque sensor with an accuracy of 0.01 Nm was used to insert the captive screw head into the plate. In the initial study, a target insertion torque of 2.50 Nm was used with the PLGA-gentamicin plate. In the control study, a target insertion torque of 1.50 Nm was used with the polylactide-triclosan plate. Each study had its own uncoated plate control group. PLGA-gentamicin plates were dip coated vertically, and results for the coated proximal and coated distal holes are displayed separately, with the coating weight being greater in the coated distal hole, which retained more suspension in the coating process. Opening torque was measured in pH 11 buffer at 37° C. for 5 days, either on the same day or after hydration and degradation of the polymer coating. The opening torque was tabulated and the % difference from the opening torque for insertion for each study group is provided in Tables 3 and 4 below.
[0072] [Table 3]
[0073] [Table 4]
[0074] As shown in Figures 3A and 3B, approximately 3.5 mg / cm in a conventional antimicrobial coating of PLGA. 2 Particulate gentamicin at 102 or 229 μg / cm interfered with the locking function of the wound plate, causing a significant reduction in the opening torque both after drying and after 5 days of incubation in pH 11 buffer. 2 The polylactide coating did not interfere with the anchoring function of the trauma plate. A 9-10% decrease in removal torque was observed during dry removal, and surprisingly, the removal torque increased upon incubation in a pH 11 buffer for 5 days.
[0075] Example 6 - Attachment and proliferation benchmark 90μg / cm with triclosan vapor transfer 2 The antibacterial colonization performance of polylactide-coated titanium alloy (titanium aluminum niobium) pins (4 mm diameter × 30 mm length) was compared to untreated TAN pins. Six coated TAN pins were placed in a foil pouch with 0.62-0.72 grams of polyethylene loaded with 2.56% triclosan. These were placed in a preheated oven at 55°C for 4 hours and 5 minutes to allow vapor transfer of triclosan from the polyethylene to the polylactide-TAN pins. Attachment and growth bacterial colonization studies were performed with S. aureus ATCC 25923 as depicted within the flow chart shown in Figure 4. To reflect the complexity of human interstitial fluid, fetal bovine serum was used as a component of the bacterial broth and levels of 0, 2% and 20% were evaluated.
[0076] Table 5 below provides the results of the evaluation. PLA-triclosan coated pins demonstrated antimicrobial activity in reducing colony formation at 24 hours despite having no effect on bacterial adhesion to the pins at 1 hour. The antimicrobial effect was greater than 4-log in liquid culture conditions, while the effect in soft agar ranged from 1.4 log-reduction in the absence of serum, to 1.9 log at 2% serum and 2.4 log at 20% serum. Without being limited to any particular theory, it is possible that the efficacy of triclosan in soft agar increased with serum content due to an increased ability to solubilize triclosan and create higher tissue concentrations of the compound. Triclosan vapor transport at 55°C for 4 hours was 90 μg / cm 2 demonstrated antibacterial efficacy when performed on polylactide-coated TAN pins.
[0077] [Table 5]
[0078] Example 7 - High heat transfer and ultra-thin films Further experimentation determined that triclosan transfer performed in an all-metal container increases the amount of triclosan transferred to the metal implant, especially when the container is made of metal or other triclosan non-absorbent material. Using such an approach, it is possible to simultaneously heat sterilize the product and impart antimicrobial properties to the target device. As demonstrated in this example, it is particularly advantageous to combine a non-absorbent package with a preferentially absorbent coating on a metal device.
[0079] To withstand the heat required for dry heat sterilization and the concomitant triclosan vapor transfer, the polymer coating must not melt or stick during the process so that it remains in its container. Poly(L-lactide), or preferably poly(D-lactide) stereocomplexed with poly(L-lactide), are candidates that remain crystalline at the relevant heat sterilization temperatures. In this example, poly(L-lactide) (Lactel B6002-2 IV:0.90-1.20) was coated onto 7-well 3.5 LCP 316L trauma plates (DPS PN223.571 98 mm long x 11 mm wide) from a 2.5% solution in chloroform at 4, 12, and 20 mm / sec. Seven sample plates were coated at each rate to accommodate three samples for triclosan quantification and one sample each for ZOI by pour plate without PBS incubation or prior elution at 1 h, 24 h, or 72 h. After dip coating and air drying, the wound plates were annealed at 130° C. to maximize the stability of the poly(L-lactide) crystalline regions.
[0080] Triclosan transfer was accomplished by depositing 1.64±0.23 mg of triclosan into each aluminum tube via solvent casting from ethyl acetate. Coated or uncoated target wound plates were inserted, the ends of the aluminum tubes were crimped closed with pliers and a vice, and triclosan transfer was then completed at 130° C. for 4 hours. Samples were removed and triclosan was quantified by UV absorbance as follows: 1.10 mg of triclosan was weighed into a 10 ml volumetric flask (amber). 2. 10 mL of solvent was then added and the powder was dissolved by vortex mixing. This was designated as the first stock concentration (1000 ppm). 3. A stock concentration of 1000 ppm of triclosan was used with subsequent dilutions in solvents such as:
[0081] [Table 6] 4. After this, 1 mL samples of each standard were transferred to plastic cuvettes and the absorbance of each sample was read in UV at 280 nm. 5. A standard curve for triclosan was then constructed by plotting absorbance at 280 nm versus triclosan concentration.
[0082] Sample preparation 1. The triclosan treated plate was placed into a sterile 15 mL centrifuge tube. 2.13 mL of acetonitrile was added to each tube. The tubes were shaken at 250 rpm for the required time. 3. After this, the pin was transferred to another sterile tube. The sample solution was stored at 4°C until analysis. 4. For analysis, the 15 ml centrifuge tubes containing the samples were vortexed briefly. 5. 1 mL of the samples were then analyzed using a UV Nanodrop instrument at a wavelength of 280 nm and the concentration of each sample was determined from the standard curve generated. Samples that showed very high initial absorbance were diluted with acetonitrile.
[0083] Figure 5 illustrates the migration of triclosan to an ultra-thin poly(L-lactide) film coated stainless steel locked compression plate in an all-metal container at 130° C. The extent of migration increased by 4.7-fold relative to the bare metal plate with the thinnest coating, and the amount of triclosan deposited was relatively insensitive to the amount of coating weight.
[0084] Table 6 below provides the poly(L-lactide) coating weight, the average triclosan transferred, and the triclosan multiplication factor for bare metal plates with dry heat sterilization and simultaneous steam transfer.
[0085] [Table 7]
[0086] The trauma plate was treated with 77, 131, and 222 μg / cm 2 The triclosan dose on the wound plate ranged from no polymer (0.24 mg) to polymer: 77 μg / cm 2 Polymer, 4.7x, 131μg / cm 2 , 5.2 times, and 222 μg / cm 2 , a 5.6-fold increase (Figure 5). When the amount of triclosan on the wound plate was expressed as a percentage of the initial triclosan in each reservoir, the ultrathin polymer coatings increased the transfer efficiency from 12% of the untreated plate to 77 μg / cm, respectively. 2 76% for the coated plate, and 131 μg / cm 2 and 222 μg / cm 2 The transfer efficiency was increased to 86% and 84% for the ultra-thin polymer coating. Due to the high transfer efficiency, the amount of triclosan deposited on the wound plate was relatively insensitive to the amount of polymer on the wound plate. This further reinforces the low manufacturing costs associated with the dip-coating process, since differences in average coating weight from plate to plate do not result in large differences in the triclosan dose transferred to the plate during dry heat sterilization and simultaneous steam transfer. The uncoated wound plate demonstrated a zone of inhibition surviving a 24-hour pre-elution in PBS, while all three ultra-thin polymer-coated plates demonstrated a zone of inhibition following a 72-hour pre-elution (Figure 6).
[0087] [Embodiment] (1) An orthopedic implant or a component of an orthopedic implant for reducing microbial growth at a surgical site, comprising: a body defining a body outer surface; a thin biodegradable polymer film disposed along at least a portion of the exterior surface of the body; a vaporizable antimicrobial agent disposed within the biodegradable polymeric film; The biodegradable polymer thin film has a thickness of about 50 to 250 μg / cm 2 or having a surface area coating weight of The vaporizable antimicrobial agent is about 5 to 85 μg / cm 2 or An orthopedic implant or a component of an orthopedic implant, wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective zone of inhibition of at least 0.5 mm from the periphery of the outer surface. (2) the surface area coating weight of the biodegradable polymer thin film is about 60 to 230 μg / cm 2 relative to the area of the surface of the body; 2 2. The orthopedic implant or component of embodiment 1, wherein (3) The orthopedic implant or component of any one of the preceding claims, wherein the biodegradable polymeric thin film comprises a poly(α-hydroxy ester) polymer. (4) The orthopedic implant or component of embodiment 3, wherein the biodegradable polymeric thin film comprises poly(glycolic acid) (PGA), poly(lactic acid) (PLA), poly(lactic-co-glycolic acid) (PLGA), poly(ε-caprolactone) (PCL), or any copolymer or mixture thereof. (5) The orthopedic implant or component of embodiment 3, wherein the biodegradable polymeric thin film comprises poly(l-lactic acid) (PLLA), poly(d-lactic acid) (PDLA), poly(d,l-lactic acid) (PDLLA), or any copolymer or mixture thereof.
[0088] (6) The antimicrobial agent is about 45 to 55 μg / cm 22. The orthopedic implant or component of embodiment 1, having a surface area concentration of (7) The orthopedic implant or component of embodiment 1, wherein the vaporizable antimicrobial agent comprises a halogenated hydroxyl ether, an acyloxydiphenyl ether, or a combination thereof. (8) The orthopedic implant or component of embodiment 1, wherein the vaporizable antimicrobial agent comprises 2,4,4'-trichloro-2'-hydroxydiphenyl ether (triclosan). (9) The orthopedic implant or component of embodiment 1, wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective zone of inhibition of about 0.5 to 4 mm from the periphery of the outer surface. (10) The orthopedic implant or component of embodiment 1, wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibition zone of about 1 to 2 mm from the periphery of the outer surface.
[0089] (11) The orthopedic implant or component of embodiment 1, wherein the surface area concentration of the antimicrobial agent is sufficient to generate an effective zone of inhibition for up to about 6, 12, 18, 24, 36, 48, or 72 hours after implantation of the orthopedic implant or component in a human subject. (12) The orthopedic implant or component of embodiment 1, wherein the biodegradable polymeric thin film is present on each surface of the body. (13) The orthopedic implant or component of embodiment 1, wherein the body comprises a metal, a polymer, or both. (14) The orthopedic implant or component of embodiment 1, wherein the body outer surface comprises a metal, a polymer, or both. (15) The orthopedic implant or component of claim 1, wherein the body exterior surface comprises polyaryletherketone (PAEK), polyalkene, metal or metal alloy, or a combination thereof.
[0090] (16) The orthopedic implant or component of embodiment 1, wherein the body outer surface comprises a metal or metal alloy. (17) The orthopedic implant or component of embodiment 16, wherein the metal is titanium, stainless steel, or an alloy containing titanium or steel. (18) The orthopedic implant or component of embodiment 1, wherein the body outer surface comprises PAEK, the PAEK being polyetheretherketone (PEEK) or a copolymer thereof. (19) The orthopedic implant or component of embodiment 1, wherein the body outer surface comprises a polyalkene, the polyalkene being polyethylene or a copolymer thereof. (20) A method for preparing an orthopedic implant or a component of an orthopedic implant that reduces microbial growth at a surgical site, comprising: applying a thin biodegradable polymer film onto a surface of the implant or an implant component; incorporating a vaporizable antimicrobial agent into said film; The vaporizable antimicrobial agent is about 5 to 85 μg / cm 2 or The method, wherein said surface area concentration of said antimicrobial agent is sufficient to produce an effective zone of inhibition of at least 0.5 mm from the periphery of said exterior surface.
[0091] (21) The biodegradable polymer thin film has a thickness of about 50 to 250 μg / cm 2 21. The method of embodiment 20, having a surface area coating weight of (22) The method according to any one of the preceding claims 20 to 21, wherein the thin film is applied to the surface of the implant or implant component by immersing the implant or implant component in a coating solution comprising the biodegradable polymer. 23. The method of claim 20, wherein the antimicrobial agent is incorporated into the film by vapor transfer from a source of the antimicrobial agent. (24) A system for reducing microbial infection at a surgical site of an orthopedic implant, comprising: an orthopaedic implant body defining an outer implant surface, the orthopaedic implant body further defining one or more openings extending through the implant body from the outer surface and configured to receive a bone fastener; a bone fastener configured to be disposed in the one or more openings to secure the orthopaedic implant body to bone, the bone fastener defining an outer fastener surface; a thin biodegradable polymeric film disposed along at least a portion of the outer implant surface or the outer fastener surface; a vaporizable antimicrobial agent disposed within the biodegradable polymeric film; The biodegradable polymer thin film has a thickness of about 50 to 250 μg / cm 2 or having a surface area coating weight of The vaporizable antimicrobial agent is about 5 to 85 μg / cm 2 or the surface area concentration of the antimicrobial agent is sufficient to produce an effective zone of inhibition of at least 0.5 mm from the periphery of the outer implant surface; Or, wherein, after use of an insertion torque suitable for implantation of the orthopedic implant body in a subject, the torque required to release the fastener from a corresponding opening in the orthopedic implant body is greater than or equal to about 90% of the torque required to release an uncoated and otherwise identical fastener from a corresponding opening in an uncoated but otherwise identical orthopedic implant body for up to five days after implantation of the orthopedic implant body in the subject. (25) A kit comprising: at least one orthopaedic implant body defining an outer implant surface, the orthopaedic implant body further defining one or more openings extending through the implant body from the outer surface and configured to receive a bone fastener; a plurality of bone fasteners configured to be disposed within at least one opening in the orthopaedic implant body to secure the orthopaedic implant body to bone, each of the bone fasteners defining a respective outer fastener surface; a thin biodegradable polymeric film disposed along at least a portion of the outer implant surface of each of the orthopaedic implant bodies, disposed along at least a portion of the outer fastener surface of each of the bone fasteners, or both; a vaporizable antimicrobial agent disposed within the biodegradable polymeric film; The biodegradable polymer thin film has a thickness of about 50 to 250 μg / cm 2 or having a surface area coating weight of The vaporizable antimicrobial agent is about 5 to 85 μg / cm 2 or the surface area concentration of the antimicrobial agent is sufficient to produce an effective zone of inhibition of at least 0.5 mm from the periphery of the outer implant surface; or wherein, after use of an insertion torque suitable for implantation of the orthopedic implant body in a subject, the torque required to release one of the fasteners from a corresponding opening in one of the orthopedic implant bodies is greater than or equal to about 90% of the torque required to release an uncoated, but otherwise identical fastener from a corresponding opening in an uncoated, but otherwise identical orthopedic implant body for up to five days after implantation of the orthopedic implant body in the subject.
[0092] (26) A method for reducing loss of release torque resulting from antimicrobial treatment of an orthopedic implant system, the orthopedic implant system comprising: an orthopaedic implant body defining an outer implant surface, the orthopaedic implant body further defining one or more openings extending through the implant body from the outer implant surface and configured to receive a bone fastener; a bone fastener configured to be disposed in the one or more openings to secure the orthopaedic implant body to bone, the bone fastener defining an outer fastener surface; The method further comprising: applying a biodegradable polymeric film to one or both of the openings and the corresponding exterior fastener surfaces; incorporating a vaporizable antimicrobial agent into said film; The biodegradable polymer thin film has a thickness of about 50 to 250 μg / cm 2 or having a surface area coating weight of The vaporizable antimicrobial agent is about 5 to 85 μg / cm 2 or the surface area concentration of the antimicrobial agent is sufficient to produce an effective zone of inhibition of at least 0.5 mm from the periphery of the outer implant surface; or wherein, following use of an insertion torque suitable for implantation of the orthopedic implant body in a subject, the torque required to release one of the fasteners from a corresponding opening in one of the orthopedic implant bodies is greater than or equal to about 90% of the torque required to release an uncoated, but otherwise identical fastener from a corresponding opening in an uncoated, but otherwise identical orthopedic implant body for up to five days following implantation of the orthopedic implant body in the subject.
Claims
1. 1. An orthopedic implant or a component of an orthopedic implant for reducing microbial growth at a surgical site, comprising: a body defining a body outer surface; a thin biodegradable polymer film disposed along at least a portion of the exterior surface of the body; a vaporizable antimicrobial agent disposed within the biodegradable polymeric film; The biodegradable polymer thin film has a thickness of 50 to 250 μg / cm 2 having a surface area coating weight of The vaporizable antimicrobial agent is 5 to 85 μg / cm 2 1. An orthopedic implant or a component of an orthopedic implant having a surface area concentration of
2. The surface area coating weight of the biodegradable polymer thin film is 60 to 230 μg / cm 2 of the area of the outer surface of the body. 2 2. The orthopaedic implant or component of claim 1 ,
3. The biodegradable polymer film comprises a poly(α-hydroxy ester) polymer, and optionally, the biodegradable polymer film comprises: (a) poly(glycolic acid) (PGA), poly(lactic acid) (PLA), poly(lactic-co-glycolic acid) (PLGA), poly(ε-caprolactone) (PCL), or any copolymer or mixture thereof; or 10. The orthopedic implant or component of claim 1, comprising: (b) poly(l-lactic acid) (PLLA), poly(d-lactic acid) (PDLA), poly(d,l-lactic acid) (PDLLA), or any copolymer or mixture thereof.
4. The vaporizable antimicrobial agent is 45 to 55 μg / cm 2 10. The orthopaedic implant or component of claim 1 having a surface area concentration of
5. The vaporizable antimicrobial agent is (a) a halogenated hydroxyl ether, an acyloxydiphenyl ether, or a combination thereof, and / or 10. The orthopedic implant or component of claim 1 comprising: (b) 2,4,4'-trichloro-2'-hydroxydiphenyl ether (triclosan).
6. The orthopedic implant or component of claim 1 , wherein the thin biodegradable polymeric film is present on each surface of the body.
7. The orthopaedic implant or component of claim 1 , wherein the body comprises a metal, a polymer, or both.
8. The body outer surface is (a) a metal, a polymer, or both; (b) a polyaryletherketone (PAEK), a polyalkene, a metal or metal alloy, or a combination thereof; (c) a metal or metal alloy, optionally wherein the metal is titanium, stainless steel, or an alloy containing titanium or steel; (d) a PAEK, the PAEK being polyetheretherketone (PEEK) or a copolymer thereof; and / or 10. The orthopedic implant or component of claim 1, comprising: (e) a polyalkene, said polyalkene being polyethylene or a copolymer thereof.
9. 1. A method for preparing an orthopedic implant or a component of an orthopedic implant that reduces microbial growth at a surgical site, comprising: applying a thin biodegradable polymer film onto a surface of the implant or an implant component; incorporating a vaporizable antimicrobial agent into said biodegradable polymeric film; the biodegradable polymer film has a surface area coating weight of 50-250 μg / cm 2 ; The vaporizable antimicrobial agent is 5 to 85 μg / cm 2 having a surface area concentration of
10. 10. The method of claim 9, wherein the biodegradable polymer film is applied to the surface of the implant or implant component by immersing the implant or implant component in a coating solution comprising a biodegradable polymer.
11. 10. The method of claim 9, wherein the vaporizable antimicrobial agent is incorporated into the biodegradable polymeric film by vapor transfer from a source of the vaporizable antimicrobial agent.
12. 1. A system for reducing microbial infection at a surgical site of an orthopedic implant, comprising: an orthopaedic implant body defining an outer implant surface, the orthopaedic implant body further defining one or more openings extending through the orthopaedic implant body from the outer implant surface and configured to receive a bone fastener; a bone fastener configured to be disposed in the one or more openings to secure the orthopaedic implant body to bone, the bone fastener defining an outer fastener surface; a thin biodegradable polymeric film disposed along at least a portion of the outer implant surface or the outer fastener surface; a vaporizable antimicrobial agent disposed within the biodegradable polymeric film; The biodegradable polymer thin film has a thickness of 50 to 250 μg / cm 2 having a surface area coating weight of The vaporizable antimicrobial agent is 5 to 85 μg / cm 2 The system has a surface area concentration of
13. A kit comprising: at least one orthopaedic implant body defining an outer implant surface, the orthopaedic implant body further defining one or more openings extending through the orthopaedic implant body from the outer implant surface and configured to receive a bone fastener; a plurality of bone fasteners configured to be disposed within at least one opening in the orthopaedic implant body to secure the orthopaedic implant body to bone, each of the plurality of bone fasteners defining a respective outer fastener surface; a thin biodegradable polymeric film disposed along at least a portion of the outer implant surface of each of the orthopaedic implant bodies, or disposed along at least a portion of the outer fastener surface of each of the plurality of bone fasteners, or both; a vaporizable antimicrobial agent disposed within the biodegradable polymeric film; The biodegradable polymer thin film has a thickness of 50 to 250 μg / cm 2 having a surface area coating weight of The vaporizable antimicrobial agent is 5 to 85 μg / cm 2 The kit has a surface area concentration of 14. A method for reducing loss of release torque resulting from antimicrobial treatment of an orthopedic implant system, comprising: an orthopaedic implant body defining an outer implant surface, the orthopaedic implant body further defining one or more openings extending through the orthopaedic implant body from the outer implant surface and configured to receive a bone fastener; a bone fastener configured to be disposed in the one or more openings to secure the orthopaedic implant body to bone, the bone fastener defining an outer fastener surface; The method further comprising: applying a biodegradable polymeric film to one or both of the openings and the corresponding exterior fastener surfaces; incorporating a vaporizable antimicrobial agent into said biodegradable polymeric film; the biodegradable polymer film has a surface area coating weight of 50-250 μg / cm 2 ; A method wherein the vaporizable antimicrobial agent has a surface area concentration of 5 to 85 μg / cm 2 .